Excessively High Hydration Volume May Not Be Associated With Decreased Risk of Contrast‐Induced Acute Kidney Injury After Percutaneous Coronary Intervention in Patients With Renal Insufficiency. Issue 6 (27th May 2016) - Liu, Yong; Li, Hualong; Chen, Shiqun; Chen, Jiyan; Tan, Ning; Zhou, Yingling; Liu, Yuanhui; Ye, Piao; Ran, Peng; Duan, Chongyang; Chen, Pingyan
Abstract : Background: No well‐defined protocols currently exist regarding the optimal rate and duration of normal saline administration to prevent contrast‐induced acute kidney injury (CI‐AKI) in patients with renal insufficiency. Methods and Results: Hydration volume ratios (hydration volume/weight; HV/W) were calculated in 1406 patients with renal insufficiency (estimated glomerular filtration rate [eGFR], <90 mL/min per 1.73 m 2 ) undergoing percutaneous coronary intervention (PCI) with routine speed hydration (1 or 0.5 mL/kg per hour). We investigated the relationship between hydration volume, risk of CI‐AKI (increase in serum creatinine ≥0.5 mg/dL or 25% within 48–72 hours), and prognosis. Mean follow‐up duration was 2.85±0.88 years. Individuals with higher HV/W were more likely to develop CI‐AKI (quartiles: Q1, Q2, Q3, and Q4: 4.3%, 6.6%, 10.9%, and 15.0%, respectively; P <0.001). After adjusting 12 confounders, including age, sex, eGFR, anemia, emergent PCI, diabetes mellitus, chronic heart failure, diuretics, contrast volume, lesions, smoking status, and number of stents, multivariate analysis showed that a higher HV/W ratio was not associated with a decreased CI‐AKI risk (Q2 vs Q1: adjusted odds ratio [OR], 1.13; Q3 vs Q1: adjusted OR, 1.51; Q4 vs Q1: adjusted OR, 1.87; all P >0.05) and even increased CI‐AKI risk (HV/W >25 mL/kg: adjusted OR, 2.11; 95% CI, 1.24–3.59; P =0.006). Additionally, higher HV/W was significantly associated with an increased risk of death (Q4 vs Q1: adjusted hazard ratio, 3.44; 95% CI, 1.20–9.88; P =0.022). Conclusions: Excessively high hydration volume at routine speed might be associated with increased risk of CI‐AKI and death post‐PCI in patients with renal insufficiency.